Analisis Usaha pembenihan Ikan Nila (Studi Kasus di BBI UPTD Budidaya Air Tawar) Desa Jantho Baru, Kabupaten Aceh Besar - Mulia Sarifah Lubis; Irwan A. Kadir; Mustafa Usman (Fakultas Pertanian, Universitas Syiah Kuala, 2021)
Aceh Besar Regency has a relatively large freshwater fishery area. Based on the 2019 BPS, it was recorded that the area of aquaculture in the Jantho area at BBI was 32.10 Ha, while the People's Breeding Unit (UPR) had an area of 15.60 Ha. BBI Jantho produces freshwater fish, namely catfish, gourami, carp, and tilapia. However, every year there is a significant increase in production, namely tilapia with a percentage increase in production of 17%. This increase occurred due to the large demand for tilapia in the market but insufficient production. The problem is that the tilapia seed market is good but the production is lacking. The purpose of this study was to analyze the feasibility of Tilapia hatchery at BBI Jantho Aceh Besar. This research is a case study using primary and secondary data. The analytical tools used are market and marketing aspects, technical and technological aspects, income analysis, Cost Ratio (R/C), Break Event Point (BEP), Return On Investment (ROI). The results of this study indicate from all aspects that this business is profitable and feasible to work on. From the technical and technological aspects, all of them meet criteria such as the location of the tilapia hatchery, the scale of operation, production activities, pond layout and inputs. The market and marketing aspects have used 1 level distribution channels. From the economic aspect where the income is Rp.69,546.042, the R/C value is 2.81, the BEP Production value is 192,270 head 540,000, the BEP value Price is Rp.71/head Rp. 200/head. The ROI value is 181% which indicates that the rate of return on capital for Tilapia Hatchery is 81% greater.